Toxicological safety evaluation of Qin-Zhi-Zhu-Dan formula in rats during the treatment and recovery periods - Xu, Wenxiu; Chen, Dan; Zhang, Zehan; Liu, Shuling; Chen, Congai; Sun, Chunyan; Ni, Wenchao; Kang, Xiangdong; Shang, Guojiao; Wang, Xueqian; Cheng, Fafeng; Wang, Qingguo (Frontiers in Pharmacology, 2022)
Background Qinzhi Zhudan Formula (QZZD), optimized from Angong Niuhuang Wan, consists of Radix Scutellariae, Fructus Gardeniae and Pulvis Fellis Suis. We had investigated the neuroprotective effects of QZZD and its active components, and demonstrated that it could treat cerebral ischemia and dementia through multiple pathways and mechanisms. Nevertheless, toxicological data on this formula still remains limited. In the study, we sought to examine the toxicological effects of QZZD during the treatment and recovery periods. Methods We investigated potential toxicities of QZZD in Sprague-Dawley rats via 28-day gavage administration. SD rats were randomly divided into control group and treatment groups of A (0.5 g/kg/d QZZD), B (1.5 g/kg/d QZZD), and C (5.0 g/kg/d QZZD). The 56-day course includes treatment period and recovery period. The rats received daily monitoring of general signs of toxicity and mortality, as well as weekly determination of body weight and food consumption. Moreover, the complete blood cell count, biochemistry, coagulation, and urine indicators, organ weights, and histopathological report were analyzed respectively at the end of the treatment and recovery periods. Results There was no death related to the active pharmaceutical ingredients of QZZD during the treatment period. The maximum no observed adverse effect level was 0.5 g/kg/d, which is approximately 16.7 times of the equivalent dose of clinical dose in rats. In group TB and TC, there were adverse effects of blue coloring of tail skin, weight loss, a significant increase of total bilirubin, blackening of liver and kidney in gross examination, hyperplasia of bile duct and karyomegaly of hepatocytes in histopathological examination. Besides, in females rats, the food consumption was reduced, while in male rats, there was decrease in triglycerides and slight increase in white blood cell count and neutrophils. In group TC, the indicators of red blood cell count, hemoglobin and hematocrit were decreased slightly, while the platelet count was increased. However, these changes were not considered to be toxicologically significant because they resolved during the recovery period. Conclusions Overall, QZZD exhibited a good safety profile.The maximum no observed adverse effect level was 0.5 g/kg/d, and no target organs toxicity were identified.